2019
DOI: 10.1111/ans.15575
|View full text |Cite
|
Sign up to set email alerts
|

Gunshot wounds to the colon: predictive risk factors for the development of postoperative complications, an experience of 172 cases in 4 years

Abstract: BackgroundIn our study, we have defined and evaluated risk factors for the development of post‐operative complications in patients with gunshot wounds to the colon. The purpose of the study is to identify the most influential risk factors.MethodsA retrospective study of 172 patients admitted with gunshot wounds to the colon from 17 February 2011 to 31 December 2014. Age, gender, shock upon admission defined by vital signs and haemoglobin level, blood transfusion, injured site of the colon, the colon injury sco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
9
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 33 publications
7
9
1
Order By: Relevance
“…In line with Busić et al and Elfaedy et al, we also demonstrated a high incidence of hemorrhagic shock in our patients suggesting such gunshot complications as a common event (10,18). Also, we have shown a higher frequency of hemorrhagic shock in patients injured by hollow-point as compared to shape-stable bullets, which is another evidence of severe trauma from the modern weapon.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…In line with Busić et al and Elfaedy et al, we also demonstrated a high incidence of hemorrhagic shock in our patients suggesting such gunshot complications as a common event (10,18). Also, we have shown a higher frequency of hemorrhagic shock in patients injured by hollow-point as compared to shape-stable bullets, which is another evidence of severe trauma from the modern weapon.…”
Section: Discussionsupporting
confidence: 92%
“…Similar to other reports, the left colon part (i.e. splenic colon exure, descending and sigmoid colon) and middle colon (ascending and descending colon) were frequently injured as compared to other sites (1,10,(20)(21)(22)(23). The importance to note that colon part injury is related to a higher risk of fecal diversion.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…As previously said, one of the most compelling reasons for making a stoma was fecal contamination; yet an increasing number of studies show that, contrary to polytransfusion, fecal contamination is not a risk factor for post-operative complications and should not be a contraindication to primary repair [23].…”
Section: Discussionmentioning
confidence: 99%